2017
DOI: 10.1007/s11356-017-8606-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects on heavy metal accumulation in freshwater fishes: species, tissues, and sizes

Abstract: Three fish species (Carassius auratus, Pelteobagrus fulvidraco, and Squaliobarbus curriculus) were collected from Xiang River near Changsha City, Southern China. The concentrations of heavy metals including arsenic (As), cadmium (Cd), copper (Cu), iron (Fe), manganese (Mn), lead (Pb), and zinc (Zn) in the muscle, gill, and liver of three species were determined by the inductively coupled plasma mass spectrometry method. One-way analysis of variance (ANOVA) was introduced to determine the significant variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
72
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(84 citation statements)
references
References 38 publications
10
72
2
Order By: Relevance
“…In combination with biogas production, liquid and solid effluent wastes from RAS have been added to the anaerobic digester for energy production, without information on the possible impact on the methanation process and a better use, such as plant fertilizer. Also considering the quality of the fish product, increasing levels of different elements in the process water finally may accumulate in the flesh of the fish [14] and affect its product quality.…”
Section: Introductionmentioning
confidence: 99%
“…In combination with biogas production, liquid and solid effluent wastes from RAS have been added to the anaerobic digester for energy production, without information on the possible impact on the methanation process and a better use, such as plant fertilizer. Also considering the quality of the fish product, increasing levels of different elements in the process water finally may accumulate in the flesh of the fish [14] and affect its product quality.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the effects of heavy metals on fishes of varying trophic levels has largely been limited to studies of differences in bioaccumulation rates and have demonstrated mixed results. Some studies from other regions with different species assemblages have demonstrated that various heavy metals are consistently present at higher concentrations within the tissues of piscivorous fishes (including fishes of the families Characidae and Ictaluridae) in comparison to fishes occupying lower trophic levels (Has‐Schön et al., ; Jia, Wang, Qu, Wang, & Yang, ; Terra, Araujo, Calza, Lopes, & Teixeira, ). In contrast, studies that have investigated bioaccumulation rates among fishes within the BRC have found that some heavy metals, such as Pb, are typically higher in lower trophic level fishes in the family Catostomidae compared to centrarchids.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] To minimize the amount of toxic ions in the environment, various approaches have been explored to remove these toxic ions from industrial effluents or water resources, including chemical precipitation, [8][9][10] electrochemical treatments, [11][12][13] ion exchange, 14,15 adsorption, [16][17][18] and so forth. Most heavy metal ions are toxic and constitute a serious health threat for humans and other species when existing in water, even at very low concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Most heavy metal ions are toxic and constitute a serious health threat for humans and other species when existing in water, even at very low concentrations. [1][2][3][4][5][6][7] To minimize the amount of toxic ions in the environment, various approaches have been explored to remove these toxic ions from industrial effluents or water resources, including chemical precipitation, [8][9][10] electrochemical treatments, [11][12][13] ion exchange, 14,15 adsorption, [16][17][18] and so forth. Among these approaches, adsorption is known to be most promising because of its convenience of operation, low cost, and availability of a diversity of adsorbent materials.…”
Section: Introductionmentioning
confidence: 99%